Enhanced environmental purification with novel Pd/ZnO nanorod–decorated building materials through piezo-photocatalytic synergistic effect - Tian, Jiayi (2024)
Integrating photocatalytic technology with building materials is an imperative new trend in the green building field. Here, a novel Pd/ZnO nanorod array-decorated ceramic tile has been designed for the first time, aiming to purify the surrounding environment. Because of the piezoelectric characteristics of ZnO nanorods, the environmental degradation efficiency of this tile-based structure under light irradiation could be improved through injecting mechanical vibration stress. The unique piezo-photocatalytic synergistic effect, due to the piezoelectric field created by bent ZnO nanorods and the Schottky junction formed by the noble metal Pd/ZnO heterostructures, could effectively separate the photoinduced carriers and reduce the rate of recombination, boosting the degradation efficiency. The tile-based Pd/ZnO reaches the greatest catalytic efficiency of 75% for dye degradation in 30 min when ultrasonic and solar irradiation are applied simultaneously. Present results offer a fresh idea for creating novel piezo-photocatalytic materials applied in eco-friendly green buildings.